(untitled) (Research, Society and Development, 2024)
Introduction: The experience of post-anesthesia care, within a complex and highly differentiated clinical context, is illustrated by clinical practice in an uncertain and variable environment, which coincides with a period of heightened vulnerability for the patient. Considering care that transcends technical operations requires a new ontological perspective rooted in human existence itself. Objective: To reflect on the nurse’s lived experience of post-anesthesia nursing care through the lens of Martin Heidegger’s essence of care. Methods: This is a theoretical-reflective analysis of post-anesthesia nursing care, focusing on the concept of care proposed by the philosopher Martin Heidegger. Conclusions: By integrating Heidegger’s phenomenological concepts into the nursing care context, care is envisioned as an existential phenomenon of being-with-others, enriched by an understanding of interaction with the world and the multiplicity of ways of being that surpass a purely technical identity.